SVM based hysteresis current controller for a three phase active power filter - Leow, Pei Ling (2004)
A space vector modulation (SVM) based hysteresis current controller (HCC) technique for a three phase shunt active power filter is proposed. The proposed SVM based HCC is implemented in a closed loop control system. The reference input to the control system is the reference compensating harmonic current. The reference compensating harmonic current is obtained from the harmonic extraction tool or called as the harmonics isolator. The harmonics extraction is based on the instantaneous active and reactive power theorem in time domain to calculate the reactive power compensation in the power system. The error current is the difference between the reference and the actual compensating harmonic current from the power compensation. Three error currents are obtained and compared by using the hysteresis tolerance band comparators to obtain the information about the region and voltage vector. The switching control algorithms of the proposed SVM based HCC manages to generate appropriate switching gates to the active power filter. The active power filter generates the actual compensating harmonic current based on the switching gates provided by the controller. The actual compensating harmonic current is generated based on the reference compensating harmonic current. The actual compensating harmonic current is then injected back into the line to cancel the harmonic components in the distorted line. By implementing this control strategy, the active power filter (APF) manages to generate better compensated harmonics currents to the line. The proposed active power filter is able to improve about 67% of the total harmonic distortion (THD) for the distorted line current caused by an uncontrolled rectifier as the nonlinear load